Formation of S0s in extreme environments I: clues from kinematics and stellar populations. Issue 2 (28th December 2019) - Coccato, Lodovico; Jaffé, Yara L; Cortesi, Arianna; Merrifield, Michael; Johnston, Evelyn; Rodríguez del Pino, Bruno; Haeussler, Boris; Chies-Santos, Ana L; Mendes de Oliveira, Claudia L; Sheen, Yun-Kyeong; Menéndez-Delmestre, Karín
ABSTRACT: Despite numerous efforts, it is still unclear whether lenticular galaxies (S0s) evolve from spirals whose star formation was suppressed, or formed trough mergers or disc instabilities. In this paper we present a pilot study of 21 S0 galaxies in extreme environments (field and cluster), and compare their spatially resolved kinematics and global stellar populations. Our aim is to identify whether there are different mechanisms that form S0s in different environments. Our results show that the kinematics of S0 galaxies in field and cluster are, indeed, different. Lenticulars in the cluster are more rotationally supported, suggesting that they are formed through processes that involve the rapid consumption or removal of gas (e.g. starvation, ram pressure stripping). In contrast, S0s in the field are more pressure supported, suggesting that minor mergers served mostly to shape their kinematic properties. These results are independent of total mass, luminosity, or disc-to-bulge ratio. On the other hand, the mass-weighted age, metallicity, and star formation time-scale of the galaxies correlate more with mass than with environment, in agreement with known relations from previous work, such as the one between mass and metallicity. Overall, our results re-enforce the idea that there are multiple mechanisms that produce S0s, and that both mass and environment play key roles. A larger sample is highly desirable to confirm or refute the results and the interpretation of this pilot study.